Highly Reversible O2 Conversions by Coupling LiO2 Intermediate through a Dual‐Site Catalyst in Li‐O2 Batteries. Issue 38 (14th August 2020) - Lin, Xiaodong; Sun, Zongqiang; Tang, Chun; Hong, Yuhao; Xu, Pan; Cui, Xueyang; Yuan, Ruming; Zhou, Zhiyou; Zheng, Mingsen; Dong, Quanfeng
Abstract: The reduction of O2 to solid Li2 O2 on discharge and the reverse oxidation of Li2 O2 to O2 on recharge are the essential processes to determine the performance of Li‐O2 batteries. The discovery of effective catalysts with a favorable Li2 O2 formation/decomposition mechanism is vital for the development of high‐performance Li‐O2 batteries. Here, a soluble catalyst of iodosylbenzene (PhIO) that can offer a highly reversible O2 conversion is reported for the first time. Benefiting from its ability to capture and couple the LiO2 intermediate, which is endowed by its polarized I 3+ O 2− bond where the I atom and O atom can serve as a Lewis acidic site and basic site (dual site) to interact with O2 − and Li +, respectively, the formation and decomposition of Li2 O2 by a one‐electron pathway can be effectively promoted, thus greatly improving the electrode surface passivation issue and the reaction kinetics. In addition, the side reactions caused by the traditional high‐reactive LiO2 intermediate can also be effectively suppressed by forming a series of low‐reactive intermediates (LiO2 3PhIO, (LiO2 )2 4PhIO, and Li2 O2 4PhIO) instead. Consequently, the PhIO‐catalyzed Li–O2 batteries exhibit a low overpotential, a large capacity, and a good cyclability. Abstract : Iodosylbenzene (PhIO) is employed as a dual‐site soluble catalyst for Li–O2 batteries. Benefiting from its ability to capture and couple the LiO2 intermediate, the solution‐phase growth and one‐electron decomposition of Li2 O2 can be greatly promoted. Moreover, the side reactions can also be effectively suppressed. Consequently, the PhIO‐catalyzed Li–O2 batteries can achieve a highly reversible O2 conversion and exhibit a superior performance.